2019
DOI: 10.5114/aoms.2018.75895
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and genetic profiling of young adults with and without a family history of premature coronary heart disease (MAGNETIC). Study design and methodology

Abstract: Introduction First-degree relatives of individuals with premature coronary artery disease (CAD) are at increased risk of CAD. The research hypothesis of this project assumes that there are differences in the metabolic profiles between individuals with and without a positive family history (FH) of premature CAD. Material and methods The study group will comprise healthy patients ( n = 500) aged 18–35 years with a FH of premature CAD, and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The following analysis is a part of the Metabolic and Genetic Profiling of Young Adults with and without a Family History of Premature Coronary Heart Disease (MAGNETIC) project, which is a case-control study that aims at analyzing classical and genetic risk factors of CAD in healthy young adults with and without a family history of P-CAD. Study design and methodology of the MAGNETIC project have been described previously [ 13 ]. In brief, the study sample was recruited between July 2015 and October 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The following analysis is a part of the Metabolic and Genetic Profiling of Young Adults with and without a Family History of Premature Coronary Heart Disease (MAGNETIC) project, which is a case-control study that aims at analyzing classical and genetic risk factors of CAD in healthy young adults with and without a family history of P-CAD. Study design and methodology of the MAGNETIC project have been described previously [ 13 ]. In brief, the study sample was recruited between July 2015 and October 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in this study were subjects from the MAG-NETIC (Metabolic and Genetic Profiling of Young Adults with and without a Family History of Premature Coronary Heart Disease) study. The design and methodology of the study have been described previously [25,26]. For the purpose of the current study, the sample was recruited between July 2015 and December 2017 ( Fig.…”
Section: Study Sample and Recruitmentmentioning
confidence: 99%
“…The study group consisted of individuals aged 18-35 years from the MAGNETIC (Metabolic And GeNETic Profiling of Young Adults with and without a Family History of Premature Coronary Heart Disease) project, who were healthy descendants of patients hospitalised in the Silesian Centre for Heart Diseases because of premature coronary artery disease (myocardial infarction or angiographically confirmed stable coronary artery disease that occurred before age 55 years in men and before 65 years in women) [20,21]. The study flow chart is shown in Figure 1.…”
Section: Study Groupmentioning
confidence: 99%